Crystallization and preliminary X-ray diffraction data of α-galactosidase from Saccharomyces cerevisiae - Fernández-Leiro, Rafael (International Union of Crystallography, 2009)

(untitled)
Saccharomyces cerevisiae α-galactosidase is a highly glycosylated extracellular protein that catalyzes the hydrolysis of α-galactosidic linkages in various glucids. Its enzymatic activity is of interest in many food-related industries and has biotechnological applications. Glycosylated and in vitro deglycosylated protein samples were both assayed for crystallization, but only the latter gave good-quality crystals that were suitable for X-ray crystallography. The crystals belonged to space group P42(1)2, with unit-cell parameters a = b = 101.24, c = 111.52 Å. A complete diffraction data set was collected to 1.95 Å resolution using a synchrotron source.